Groundwater carbon within a boreal catchment - spatiotemporal variability of a hidden aquatic carbon pool - Nydahl, Anna (Uppsala University, 2019)
Groundwater is an essential resource providing water for societies and sustaining surface waters. Although groundwater at intermediate depth could be highly influential at regulating lake and river surface water chemistry, studies quantifying organic and inorganic carbon (C) species in intermediate depth groundwater are still rare. Here, we quantified dissolved and gaseous C species in the groundwater of a boreal catchment at 3 to 20 m depth. We found that the partial pressure of carbon dioxide (pCO2), the stable carbon isotopic composition of dissolved inorganic carbon (δ13C-DIC) and pH showed a dependency with depth. δ13C-DIC, and between pCO2 and pH. We attribute the negative pCO2-pH relationship along the depth gradient to increased silicate weathering and decreased soil respiration. Silicate weathering consumes carbon dioxide (CO2) and release base cations, leading to increased pH and decreased pCO2. We observed a positive relationship between δ13C-DIC and depth, potentially due to diffusion-related fractionation in addition to isotopic discrimination during soil respiration. Soil CO2 may diffuse downward, resulting in a fractionation of the δ13C-DIC. Additionally, the dissolved organic carbon (DOC) at greater depth may be recalcitrant consisting of old degraded material with a greater fraction of the heavier C isotope. Our study provides increased knowledge about the C biogeochemistry of groundwater at intermediate depth, which is important since these waters likely contribute to the widespread CO2 oversaturation in boreal surface waters.

Data set for a study we quantified dissolved and gaseous carbon species in the groundwater across a mesoscale boreal catchment at depths between 3 and 20 m.

The study was carried out within the 68 km² large Krycklan Catchment area (64°14′N, 19°46′E) located in the boreal region of northern Sweden. Sampling was performed in the main Krycklan catchment (C16) and five sub-catchments (C2, C7, C8, C9 and C13). Groundwater was collected from 16 wells, at depths ranging from 3.4 to 19.5 m. The diameter of each groundwater well is 8.7 cm. Sampling was performed at three different occasions (summer, autumn and spring). Summer sampling took place on the 12ᵗʰ to 16ᵗʰ of June 2017, autumn sampling on the 11ᵗʰ to 15ᵗʰ of September 2017 and spring sampling on the 7ᵗʰ to 11ᵗʰ of May 2018. The water level in each well was measured before sampling to allow calculation of the total volume of water in the well. Prior to sampling at least three times the volume of the well of water was removed using a submersible centrifugal pump such that only the new infiltrating water was used for analysis. Groundwater was collected from approximately 10 cm above the bottom of the well.

For the partial pressure ofCO₂ (pCO₂), triplicate samples of 30 mL were taken with a 60 mL syringe. For dissolved inorganic carbon (DIC) and methane (CH₄) determination, a 5 ml sample of bubble-free water was taken directly from the pump-connected tube using a sterile syringe, which was flushed with groundwater before sampling. For δ¹³C-DIC determination, a 2 ml water sample was injected into a helium flushed 12 ml bromobutyl septa capped Exetainer glass vial. Samples for dissolved organic carbon (DOC) were collected without headspace in 250 ml acid washed high-density polyethylene bottles.

Analysis of pCO₂ was conducted in the field using the headspace equilibrium method. Equilibrated gas samples were analyzed on a portable infrared gas analyzer . Headspace CO₂ and CH₄ concentrations were analyzed by a GC‐FID. Concentrations of DIC and CH₄ were then calculated from the GC determined headspace of pCO₂ and partial pressure of CH₄ (pCH₄). For δ¹³C-DIC, samples of 100 µL headspace gas were analyzed using an isotope ratio mass spectrometer. The DOC was measured as total organic C (TOC) on a Shimadzu TOC-VCPH. The pH was analyzed using a closed pH cell to avoid any outgassing of CO₂ and measured with a Mettler Toledo Digi117-water combined pH meter

Version 2. 2019-11-28

The dataset was originally published in DiVA and moved to SND in 2024.

Dataset för en studie där vi kvantifierade upplösta och gasformiga kolarter i grundvattnet över ett mesoskaligt borealt avrinningsområde på djup mellan 3 och 20 m. Se engelsk version av denna katalogpost för ytterligare beskrivning.

Version 2. 2019-11-28
Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Groundwater carbon within a boreal catchment - spatiotemporal variability of a hidden aquatic carbon pool
Keywords: stable carbon isotopic composition of dissolved inorganic carbon; stable carbon isotopic composition of dissolved inorganic carbon; Biology with specialization in Limnology; Biology with specialization in Limnology; dissolved inorganic carbon; dissolved inorganic carbon; dissolved organic carbon; dissolved organic carbon; carbon dioxide; carbon dioxide; carbonate system; carbonate system; Biological Sciences; Biologi